Python algorithms in particle tracking microrheology - Maier, Timo; Haraszti, Tamás (Chemistry central journal, 2012)
Particle tracking passive microrheology relates recorded trajectories of microbeads, embedded in soft samples, to the local mechanical properties of the sample. The method requires intensive numerical data processing and tools allowing control of the calculation errors.
Gesehen am 16.08.2018